PENGARUH KOMPENSASI DAN SEMANGAT KERJA TERHADAP PRODUKTIVITAS PEGAWAI DIKANTOR CAMAT TELUKDALAM - Obertin Trimulyani Telaumbanua (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
This type of research is quantitative. Sources of data were obtained from 31 employees and casual daily workers. The data collection technique in this study was by distributing questionnaires as a research instrument to all employees and casual daily workers. The data analysis technique in this study used multiple regression analysis. The results of this study indicate that there is an effect of compensation and work enthusiasm on employee productivity as evidenced by the Fcount value of 6,967 > Ftable of 3.328 and a significant level of 0.004 <0.05. Thus, it is shown that compensation and work morale have a positive and significant effect on employee productivity at the Teluk Dalam Sub-District Office.